221k views
5 votes
How to solve :
y = 6x-5
y = -x+9
by substitution method???

1 Answer

4 votes

Answer:

(2,7)

Explanation:

y = 6x - 5

y = -x + 9

ok...so y = 6x - 5...so sub 6x - 5 in for y back in the 2nd equation

6x - 5 = -x + 9....add x to both sides

6x + x - 5 = 9....add 9 to both sides

6x + x = 9 + 5 ....combine like terms

7x = 14....divide both sides by 7

x = 14/7...reduce

x = 2

now sub 2 in for x in either of ur original equations and find y

y = 6x - 5

y = 6(2) - 5

y = 12 - 5

y = 7

and u can check ur answer by subbing ur answer back into either of both of the original equations

y = -x + 9

7 = -2 + 9

7 = 7 (correct)...so it checks out

ur solution is : x = 2 and y = 7 or (2,7)

User Matthew Warman
by
4.9k points